PERAN LINGKUNGAN SOSIAL MASYARAKAT DALAM PEMBENTUKAN KARAKTER BELAJAR PESERTA DIDIK DI MIN 2 PADANGSIDIMPUAN - Efridawati Harahap (DIRASATUL IBTIDAIYAH, 2023)
Writing research has the intention to understand and know the influence of the social environment of society in the formation of students' learning character. The method used in this journal uses the library research method, which is carried out by citing sources from scientific writings. The result of this scientific writing is an assessment of several papers regarding the influence of the social environment in the formation of students' learning character. This library research study method is used to collect various information and data regarding the material being studied to be a reference for the results obtained. To conduct a library research study, steps are needed such as collecting references that are in accordance with the sections to be discussed, looking for discussions that are appropriate and related to writing this journal, and analyzing the contents of the sources obtained. The data analysis techniques used were clarifying, combining, and concluding. The results of research on the influence of the social environment in the formation of the learning character of students: 1) understanding the influence of the social environment; 2) the formation of the character of students in learning.Â Keywords: Social Environment; Â Society; Character of Students.